Professionals forecasting inflation: The role of inattentiveness and uncertainty - Joshy Z. Easaw; Roberto Golinelli; Saeed M. Heravi (Cardiff University, Cardiff Business School, 2022)
The purpose of this paper is to investigate the nature of professionals' inflation forecasts inattentiveness. We introduce and empirically investigate a new generalized model of inattentiveness due to informational rigidity. In doing so, we outline a novel model that considers the non-linear relationship between inattentiveness and aggregate uncertainty, which crucially distinguishes between macro-economic and data ( measurement error) uncertainty. The empirical analysis uses the Survey of Professional Forecasters data and indicates that inattentiveness due to imperfect information explains professional forecasts' dynamics.
Keywords: E3; E4; E5; 330; Inflation Forecasts; Information Rigidities; Inattentiveness; Uncertainty; Survey Forecasts